Pandemic influenza A (H1N1) in Saudi Arabia: description of the first one hundred cases - AlMazroa, Mohammad A. (Medknow Publications, 2010)
BACKGROUND AND OBJECTIVES: In April 2009, the World Health Organization (WHO) declared pandemic influenza A (H1N1) “public health emergency of international concern”. On June 11, 2009, WHO raised the pandemic alert level to phase 6, indicating a global pandemic. By December 2009, more than 208 countries and territories had reported swine flu cases. The descriptive epidemiology of the first reported 100 cases of this virus in Saudi Arabia are summarized in this report. METHODS: Data were collected from 1 June to 3 July, 2009 using a predesigned questionnaire. Questionnaires were filled by Field Epidemiology Training Program residents. Data for the first 100 complete cases of confirmed pandemic influenza A (H1N1) were compiled and analyzed. RESULTS: The age of reported cases was in the range of 1 to 56 years. The highest percentage of cases was in the age group of 20 to 30 years followed by the age group of 1 to 10 years. Females represented 55% of the cases; imported cases represented 47%, 58% of whom had come via the King Khaled Airport. The most common nationalities most were from Saudi Arabia and the Philippines. The main symptoms were fever (56%), cough (54%), and sore throat and the number of cases was seen to peak from the 27 to 29 June. CONCLUSION: Pandemic influenza A (H1N1) is still a threat to Saudi Arabia. Thus, comprehensive and effective measures for surveillance and prevention of the disease are needed to control its spread.